Ultra-high performance recycled steel fiber reinforced concrete segments under the thrust force of TBM jacks and their environmental potentialities. (January 2023) - Gholami, Esmail; Afshin, Hassan; Charkhtab Basim, Mohammad; Sharghi, Mohammad
Abstract: Investigations have indicated that segmental tunnel linings are mainly affected during their installation phase, especially at the stage of applying thrust force. Although these concentrated thrust forces are applied temporarily, they can cause cracks and serious damage to segments. One of the main goals of this research is to evaluate the performance of ultra-high performance fiber reinforced concrete (UHPFRC) using recycled steel fibers (RSF) in tunnel lining segments. An experimental and numerical research program, including small-scaled segments (panel samples), was developed to achieve this goal. In this program, an axial load equivalent to the thrust force of a tunnel boring machine (TBM) is applied to 4 different types of samples. Three common states of defects in the support area have also been simulated to examine the more accurate and realistic performance of segment specimens. Another goal of this research is to present a hybrid design for tunnel segments using UHPFRC with RSF in order to significantly reduce the consumption of reinforcement rebar despite the significant increase in the performance of tunnel segments. Based on the results obtained, it was observed that UHPFRC segments with RSF have a good ability to reduce the opening and growth of cracks caused by the thrust forces. The new hybrid reinforced designs have shown significantly better performance compared to the conventional reinforced segments. Crack openings, the first crack starting force, and the environmental friendliness in the full-recycled fiber UHPFRC segments and two new hybrids reinforced samples were improved compared to the conventional reinforced design.